Clinical effect of closed reduction minimally invasive fixation in intra-articular comminuted fractures of the femoral condyle - Lian, Xiaodong; Zhang, Heng; Guo, Fan; Wang, Zhongzheng; Zhao, Kuo; Hou, Zhiyong; Zhang, Yingze (Frontiers in Surgery, 2023)
Objective: To evaluate the advantages of double reverse traction closed reduction combined with minimally invasive fixation in treating femoral condylar comminuted fractures. Methods: We retrospectively enrolled a total of 24 patients with femoral condylar comminuted fractures (AO=33C3) admitted to Third Hospital of Hebei Medical University from March 2018 to February 2020. The patients were divided into two groups: experimental group (double reverse traction, n = 12) and control group (conventional surgery, n = 12). Patient demographics, fracture characteristics, operation time, incision length, and postoperative complications were then collected. The Hospital for Special Surgery (HSS) scores were recorded at the last follow-up visit. Results: The average surgical time was 52.2 (41-73) min in the experimental group and 71.2 (45-103) min in the control group. In addition, the mean total incision length was 13.8 (11-17) cm in the experimental group and 16.3 (14-19) cm in the control group. The average HHS scores at the final follow-up were 86.3 (78-93) and 82.7 (76-90) in the experimental group and control group, respectively. Conclusion: It was found that double reverse traction closed reduction combined with minimally invasive fixation can provide good repositioning results and functional extremity. Moreover, patients tolerate postoperative functional knee exercises well.